The use of Waste Sieving Tools to Support the Waste Composting Process In the Campus 7 of Health Polytechnic of Ministry of Health Semarang - Suparmin Suparmin; Sugeng Abdullah; Wahyu Putriyantari (Buletin Keslingmas, 2020)
Introduction: Campus 7 Health Polytechnic of the Ministry of Health Semarang, is an educational institution that is integrated with a canteen, housing for lecturers and has an open area of 2.3 ha where organic waste is generated on average 4 m3 / week and an average of 0.85 inorganic waste m3 / week predominantly plastic. Campus 7 as an educational institution in which there is a Department of Environmental Health and has qualified human resources (HR) in the field of waste processing has pioneered a composter pilot unit with the run way method which is arranged in 10 basins. Based on the description above, the formulation of the problem in this study is to determine the effectiveness of the compost sieve engineering tool in supporting the waste processing process. Methods: Pre-experiment with Post Test Only Design research design. With the design of tools for comparing the results before and after using the tools used. This research was conducted at a waste processing place (composter) at Campus 7 Poltekkes Kemenkes Semarang. The population in this study is all of the waste generation from campus 7 residents . The sample of this research is the waste contained in the final tub (10th) of compost processing, with a volume of 0.5-1 m3 / week. The data analysis used in this research is table analysis and the average value calculated from the results of sieving the waste. Result and discussion: Research and Development is a research method that uses to obtain or develop products and test the effectiveness of these products. The volume of waste from the end of final processing (tub 10) is around 531.2 liters (238.5 kg). The amount of plastic waste that was sorted manually was 176 lt (43.5 kg), so the amount of waste that needed to be sieved was around 355.2 liters (195 kg). Comparison of the results of manual sifting of waste takes about 75 minutes with 3 workers, it is obtained that the waste is separated into 3 parts as follows : Plastic waste by the size 5cm (24.5 kg), large compost waste by the size 5cm s. D 1 cm by 94.4 lt (53kg) and small compost by the size   1cm by 188.8 lt (117.5 kg). Sifting capability is approximately 4,74 lt/ minute (2.6 kg/ minute). Machine-sifting takes about 23 minutes with 2 workers, collected waste into 4 parts as follows: plastic trash by the size 5cm as much as  73.6 lt (33.05 kg), large composite waste and plastic D 2cm as much as 61% lt (27.39 kg), huge compost waste D 1 cm as much as 35 lt (15.715 kg) and a small compost measure 1cm as much as 185.6 lt (83.33 kg). The capability of sifting about 1544 lt/ minute (8.5 kg/ minute)